PENERAPAN ELEKTROKOAGULASI DALAM PROSES PENJERNIHAN LIMBAH CAIR - Eddy Wiyanto; Budi Harsono; Amelia Makmur; Rudy Pangputra; Julita Julita; Mario Stefanus Kurniawan (Jetri : Jurnal Ilmiah Teknik Elektro, 2014)
Environmental problems has become a global issue and need a serious attention. Not only solid waste, liquid waste also have negative effects on the environment and human health. The existence of these needs must be balanced with the development of wastewater treatment technologies, both for liquid waste from factories, hospitals, and other sources. Various methods have been applied to solve the problem of liquid waste, mostly using a chemical process by reaction with chemicals. Purification of waste water by chemical processes have various shortcomings. Another alternative is the principle of electrocoagulation. Electrocoagulation is a process of coagulation or clotting of the electrical power through the process of electrolysis to reduce the metal ions and particles in the water. The basic principle of electrocoagulation is a reduction and oxidation (redox). This research will be designed a tool that applies the principles of electrocoagulation for wastewater purification process with the development of several existing tools of electrocoagulation, which is portable, it can eliminate many kinds of pollutants, including heavy metals that are dangerous, using bubble system as binding contaminants, more stronger than the floc Al (OH) 3, and use the Self-Cleaning system with a reverse voltage so that the cleaning process can reduce operational costs.  Keywords: waste water, electrocoagulation, electrodes, self-cleaning systemMasalah lingkungan telah menjadi isu global dan perlu mendapat perhatian serius. Tidak hanya limbah padat, limbah cair juga memiliki efek negatif terhadap lingkungan dan kesehatan manusia. Adanya kebutuhan ini perlu diimbangi dengan pengembangan teknologi pengolahan air limbah, baik untuk limbah cair dari pabrik, rumah sakit, dan sumber lainnya. Berbagai metode telah diterapkan untuk menyelesaikan masalah limbah cair, sebagian besar menggunakan proses dengan reaksi bahan kimia. Pemurnian air limbah dengan proses kimia memiliki berbagai kekurangan. Alternatif lain adalah menggunakan prinsip elektrokoagulasi. Elektrokoagulasi adalah proses koagulasi atau penggumpalan dengan daya listrik melalui proses elektrolisis untuk mengurangi ion logam dan partikel di dalam air. Prinsip dasar dari elektrokoagulasi adalah reduksi dan oksidasi (redoks). Pada penelitian ini akan dirancang sebuah alat yang menerapkan prinsip-prinsip elektrokoagulasi untuk proses pemurnian air limbah dengan pengembangan terhadap alat elektrokoagulasi yang telah ada, yaitu bersifat portabel, dapat menghilangkan berbagai jenis polutan, termasuk logam berat yang berbahaya, menggunakan sistem gelembung sebagai pengikat kontaminan, yang lebih kuat daripada flok Al(OH)3, dan menggunakan sistem Self-Cleaning dengan tegangan balik dimana proses pembersihan dapat dilakukan secara otomatis sehingga mengurangi biaya operasional.  Kata kunci: air limbah, elektrokoagulasi, elektroda, sistem self-cleaning